Inside Back Cover: Li/air Flow Battery Employing Ionic Liquid Electrolytes (Energy Technol. 1/2016). Issue 1 (11th November 2015) - Grande, Lorenzo; Ochel, Anders; Monaco, Simone; Mastragostino, Marina; Tonti, Dino; Palomino, Pablo; Paillard, Elie; Passerini, Stefano
Abstract : Go with the Flow: The need for better batteries has fueled research in high‐risk/high‐reward cell chemistries such as lithium/air. This technology has the potential to enable a new generation of electric vehicles that can travel long distances while keeping the dimensions of the battery pack reasonably small. Before Li/air batteries can make it onto the market though, several fundamental questions need to be addressed, such as the (electro)chemical stability of their components during cycling and the evaporation of the electrolyte (cell drying), which can expose the reactive lithium metal to the atmosphere. The authors have tried to address all of the above‐mentioned points by developing and scaling up a novel two‐phase Li/O2 flow battery. This device can operate under mild conditions thanks to the use of a non‐volatile ionic‐liquid‐based electrolyte, and its performance can be improved by raising the temperature up to 60 °C, without incurring any decomposition or cell drying. With the aid of an oxygen‐bubbling device, the flow cell design keeps the O2 concentration constant, thereby obviating diffusion‐related limitations, as well as ensuring that the whole cathode active area is effectively participating in the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) processes. Moreover, the high mass loadings attained with the use of purpose‐designed mesoporous carbons helps achieve high areal capacities (up to 4.78 mAh cm ‐2 ), which, together with the self‐contained configuration, make the Li/O2 flow cell an appealing configuration for automotive applications. More details can be found in the Full Paper by Grande et al. from Helmholtz Institute Ulm and several other institutes in Germany, Italy, and Spain onpage 85 in Issue 1, 2016 (DOI:10.1002/ente.201500247 ).